Salivary cortisone, as a biomarker for psychosocial stress, is associated with state anxiety and heart rate. (March 2019) - Bae, Yoon Ju; Reinelt, Janis; Netto, Jeffrey; Uhlig, Marie; Willenberg, Anja; Ceglarek, Uta; Villringer, Arno; Thiery, Joachim; Gaebler, Michael; Kratzsch, Juergen
Highlights: Healthy men completed either the Trier Social Stress Test or a Placebo-TSST. High discrimination between two groups was shown in salivary cortisone. Salivary cortisone was associated with state anxiety level and heart rate. Discriminatory power of stress markers was dependent on the time from stress onset. Abstract: Background: Stress activates the central nervous, the autonomic nervous, and the endocrine system. This study aimed to (1) test the usability of salivary cortisone in a standardized psychosocial stressor, (2) create a comprehensive profile of hormonal responses to determine laboratory parameters with high discriminatory power, and (3) analyze their association with psychometric and autonomic stress measures. Methods: Healthy young men (18–35 years) completed either the Trier Social Stress Test (TSST) (n = 33) or a Placebo-TSST (n = 34). Blood and saliva were collected at 14 time points along with state-anxiety (STAI) and heart rate. Serum steroids (cortisol*, cortisone*, dehydroepiandrosterone-sulfate, androstenedione*, progesterone*, 17-hydroxyprogesterone*, testosterone, estradiol*, aldosterone*), salivary cortisol* and cortisone*, copeptin*, adrenocorticoptropic hormone*, corticosteroid-binding globulin, and salivary alpha-amylase* were analyzed. We used mixed-design ANOVAs to test group differences, receiver operator characteristic (ROC) curve analyses to assess the discriminatory power of each measure, and Spearman correlation analyses to probe the association between measures. Results: The largest area under the ROC curve was observed in salivary cortisone at 20 min after the end of the TSST (AUC = 0.909 ± 0.044, p < 0.0001). Significant time-by-group interactions were found in the parameters marked with * above, indicating stress-induced increases. The peak response of salivary cortisone was significantly associated with those of STAI (rho = 0.477, p = 0.016) and heart rate (rho = 0.699, p < 0.0001) in the TSST group. Conclusion: Our study found salivary cortisone to be a stress biomarker with high discriminatory power and significant correlations with subjective and autonomic stress measures. Our results can inform future stress studies of sampling time for different laboratory parameters.